The Importance of Habitus Changes in Community Empowerment (A Case Study of Milk and Fodder Processing in Slumut, Kumpulrejo Village, Salatiga, Central Java Province) (Faculty of Social Science, Universitas Negeri Semarang, 2021)
In carrying out economic empowerment, the role of actors as other parties is needed to help the community develops their potential. The role of the actor in Pierre Bourdieu's perspective consists of shared capital with habitus. This study would like to find out the relation between the success role of actors and the provision of economic, social, and cultural capital along with changes in habitus. This research was conducted in Slumut, Kumpulrejo Village, Salatiga. This location has two main potentials, namely milk and cattle fodder/concentrate feeds processing. The actors involved in economic empowerment in Slumut, Kumpulrejo Village, were the Department of Agriculture and Livestock from the government sector and the NGO Idea from the non-government sector. The two of them assist the Farmers Group of Margoraharjo 4. The research method used is descriptive qualitative with observation techniques, in-depth interviews, and document review. The results of this study indicate that although the actors have provided capital assistance, the community's habitus is difficult to change. Raising cattle is a hereditary job that forms habitus. They are content with what is now. People do not have enough effort to reach new markets and make variations in dairy products, which means they must have a new habitus. This makes it difficult for the government to support the development of milk and cattle fodder/concentrate feed processing businesses. The results of this study indicate that it is difficult for the community to change its habitus.